2018
DOI: 10.1177/0034644618822500
|View full text |Cite
|
Sign up to set email alerts
|

We’ve to Build the Pipeline. What’s the Problem? What’s Next? The Remix

Abstract: Despite a history of initiatives to strengthen the doctorate pipeline and mentoring programs for graduate students and junior faculty, the economics profession has failed to achieve a representative level of diversity across ethnicity, gender and race. This National Economic Association presidential address looks at the 20-year production, 1996-2015, of economists by ethnicity, gender, race, and residential status with an interest in the production of Black economists. The findings suggest there is cause for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…As we have noted, these findings are probably biased in favor of those who have experienced upward mobility and may have followed the White normative logics of academia. Likewise, a substantial minority seem to have obtained positions at research extensive institutions, despite processes, biases, and perceptions that may work against them, notwithstanding their qualifications (Sharpe, 2017).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…As we have noted, these findings are probably biased in favor of those who have experienced upward mobility and may have followed the White normative logics of academia. Likewise, a substantial minority seem to have obtained positions at research extensive institutions, despite processes, biases, and perceptions that may work against them, notwithstanding their qualifications (Sharpe, 2017).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Whether the focus should be on doctorate-granting departments is debatable. More recently, Sharpe (2018) has argued that the emphasis on diversifying the economics pipeline should focus on the departments that award the bachelor's degree.…”
Section: About the Authorsmentioning
confidence: 99%
“…Whether diversity efforts are focused on at the undergraduate or graduate level, the consequences of the 'colour line' were revealed in the 2019 American Economic Association (AEA) Climate Survey, which found that 43 % of Black men and 53% of Black women reported experiencing discrimination based on their race. It is unclear whether the lack of Blacks in the economics profession has intensified the hostile environment for Black economists at all stages of the profession, but there is evidence that suggests the discrimination felt by Black women has led to a decrease in the number of Black women pursuing an economics degree at the undergraduate level (Sharpe 2018.…”
Section: About the Authorsmentioning
confidence: 99%
“… 2. Past National Economic Association (NEA) President Rhonda Sharpe (2018) called for these very same things in her 2018 address. …”
mentioning
confidence: 99%